2021
DOI: 10.1002/cac2.12187
|View full text |Cite
|
Sign up to set email alerts
|

Squalene epoxidase promotes colorectal cancer cell proliferation through accumulating calcitriol and activating CYP24A1‐mediated MAPK signaling

Abstract: Background Colorectal cancer (CRC) is one of the most malignant tumors with high incidence, yet its molecular mechanism is not fully understood, hindering the development of targeted therapy. Metabolic abnormalities are a hallmark of cancer. Targeting dysregulated metabolic features has become an important direction for modern anticancer therapy. In this study, we aimed to identify a new metabolic enzyme that promotes proliferation of CRC and to examine the related molecular mechanisms. Methods We performed RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 67 publications
(69 reference statements)
2
47
0
Order By: Relevance
“…Moreover, a positive correlation between intestinal intact breaking bacteria E.Coli and A.Muciniphila and cholesterol in MNCs further indicating that up-regulation of cholesterol is associated with intestinal break. As we all know, SQLE is a key enzyme in cholesterol biosynthesis, which has been reported to be oncogenic in several disease [25,26]. Our study fulfills a further recognition of SQLE in AML.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, a positive correlation between intestinal intact breaking bacteria E.Coli and A.Muciniphila and cholesterol in MNCs further indicating that up-regulation of cholesterol is associated with intestinal break. As we all know, SQLE is a key enzyme in cholesterol biosynthesis, which has been reported to be oncogenic in several disease [25,26]. Our study fulfills a further recognition of SQLE in AML.…”
Section: Discussionsupporting
confidence: 83%
“…In our previous study, we found that SQLE promoted colon cancer cell proliferation in vitro and in vivo 25 . Squalene synthase functions upstream of SQLE in the steroid synthesis pathway.…”
Section: Resultsmentioning
confidence: 92%
“…In our previous study, we found that SQLE promoted colon cancer cell proliferation in vitro and in vivo. 25 Squalene synthase functions upstream of SQLE in the steroid synthesis pathway. Accordingly, we generated the FDFT1/SQLE double-KD HT29 cell line to explore the possibility of the combined functions of FDFT1 and SQLE on colon cancer cell proliferation.…”
Section: Squalene Synthase Synergized Sqle To Accelerate Proliferatio...mentioning
confidence: 99%
“…Higher expression of LPCAT1 in CRC patients is associated with worse prognosis [48]. Among the genes and gene combinations mentioned in the Table 8, knock down effects of only the first two, PTGS2 and SQLE have been studied in CRC cell lines and animal models [41, 47]. The other proposed targets are found to have an effect on CRC cell line based on the negative log fold values from DEMETER database but are yet to be studied as gene targets in different CRC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The other proposed targets are found to have an effect on CRC cell line based on the negative log fold values from DEMETER database but are yet to be studied as gene targets in different CRC cell lines. PTGS2 is over-expression is correlated with a lower survival rate among CRC patients [41] Squalene monoxygenase (cholesterol synthesis) SQLE stimulates CRC cell proliferation by regulating the cell cycle and its overexpression is associated with poor prognosis in CRC patients in the primary stages [47] 1-Acylglycerol-3-phosphate O-acyltransferase (fatty acid metabolism) LPCAT1 stimulates CRC development by enhancing membrane biosynthesis and its a risky prognostic gene in CRC patients [48,49] Linoleoyl-CoA desaturase (fatty acid synthesis) Upregulation of FADS2 promotes colon cancer proliferation and tumor growth and yet to be explored as CRC target [43] Carbonyl reductase (xenobiotics metabolism and antioxidant defense)…”
Section: Validating the Predicted In-silico Gene Targetsmentioning
confidence: 99%